Issues of Religion in Nepal - Adhikari, Rishiram (International Research Journal of MMC, 2022)
Religion is one of the identities markers of the nation. In republic Nepal, the issue of religion appears as political and cultural agenda for both political and religious leaders. In this context, the paper examines focuses on the historical landmarks of debate on religions in Nepal and how different constitutions address the religious issues and why they are becoming emerging issues in Nepal. Qualitative research designwas used and only secondary sources of data were applied for this study. Conclusion of the studyis based on data interpretation and analysis. In the past, religion was used as atool to gain political powerthat has still being continuedbecause some of the political party 'leaders still use religion as a tool of collecting votes from the public.